EFFECT OF ALGAE SEAWEED, URTICA DIOICA AND ZINC SULFATE ON SOME YIELD QUALITY AND CHEMICAL PARAMETERS OF BROCCOLI (BRASSICA OLERACEA VAR. Italica) PLANT - MOHAMMED, MUSTAFA OMAR; SARHAN, TAHA Z. (Journal of Duhok University, 2023)
This study was carried out in an unheated plastic house of the vegetable research farm of Protected Cultivation Department in Zakho Technical Institute/Dohuk Polytechnic University on Broccoli (Brassica oleracea var. italica) plant on the period from 1st September 2021 to 1st April 2022, to study the effect of three levels of Algae Seaweed concentration (0, 4, and 8 ml L-1), three levels of Urtica dioica (0, 4 and 8 ml L-1) and three levels of Zinc Sulfate (0, 5, 10 g L-1). The results showed that increased Algae seaweed concentrations caused significantly increased head length, head diameter, total Chlorophyll, nitrogen% in leaves, phosphorus% in leaves, protein% and carbohydrates % in heads. In the same time the increased Urtica dioica concentrations caused significantly increased in most of studied parameter except total chlorophyll and carbohydrates % so as zinc sulfate which increased in most of studied parameter except carbohydrates %. The best interaction which observed among the three factors was (Algae Seaweed 8 mL-1, Urtica dioica 8 mL-1 and zinc sulfate 10 gL-1) that gave the highest means for the most of the studied parameters compared with control